Design and synthesis new indole-based aromatase/iNOS inhibitors with apoptotic antiproliferative activity - Al-Wahaibi, Lamya H.; Abou-Zied, Hesham A.; Abdelrahman, Mostafa H.; Morcoss, Martha M.; Trembleau, Laurent; Youssif, Bahaa G. M.; Bräse, Stefan (Frontiers in Chemistry, 2024)
The present study details the design, synthesis, and bio-evaluation of indoles 3-16 as dual inhibitors of aromatase and inducible nitric oxide synthase (iNOS) with antiproliferative activity.the study evaluates the antiproliferative efficacy of 3-16 against various cancer cell lines, highlighting hybrids 12 and 16 for their exceptional activity with GI50 values of 25 nM and 28 nM, respectively. The inhibitory effects of the most active hybrids 5, 7, 12, and 16, on both aromatase and iNOS were evaluated. Compounds 12 and 16 were investigated for their apoptotic potential activity, and the results showed that the studied compounds enhance apoptosis by activating caspase-3, 8, and Bax and down-regulating the anti-apoptotic Bcl-2. Molecular docking studies are intricately discussed to confirm most active hybrids' 12-and 16-binding interactions with the aromatase active site. Additionally, our novel study discussed the ADME characteristics of derivatives 8-16, highlighting their potential as therapeutic agents with reduced toxicity.